Nor-tec Rifa! : Electronic Dance Music from Tijuana to the World. - Madrid, Alejandro L. (Currents in Iberian and Latin American Music., 2008)
List of Figures. List of Music Examples. Acknowledgements. Introduction: Nor-tec and the Borders. 1. Origins Revisited. Myth and Discourse in the Nortec Collective. 2. Tradition, Style, Nostalgia, and the Kitsch. 3. Getting the Word Around. 4. "Where is the Donkey Show Mr. Mariachi?" Reterritorializing TJ. 5. Producers, DJs, Fans, and the Performance of Nor-tec. 6. Dancing with Desire. 7. Nor-tec and the Postnational Imagination. Bibliography.